International organizations as law-makers - Alvarez, José E. (O.U.P. OxfordGB, 2005)
Examines select examples of international organization (IO) activity whose normative impact is often ignored or under-estimated within three broad categories viz. international law; treaty-making conducted under IO auspices; and, institutionalized dispute settlement.